Biofortification: A plausible antidote to hidden hunger - Kumar, Niraj; Kumar, Anjani (Indian Express Group, 2019)
A dip in India’s ranking in the Global Hunger Index (GHI) has rightly created a stir in the country. The continued focus on calories, and the ignorance of nutritional aspects of food are responsible for the distressed state of the food and nutrition system in our country. The present ranking is an outcome, and a true reflection, of the same. A few in the government appear to be shocked and have even questioned the methodology. Why is India, even after 72 years of independence, struggling at the bottom of the GHI rankings? It is high time that we look deeper into the issue and find a plausible solution to the dire straits we are in.